The little Paris bookshop [large type] : a novel - George, Nina, 1973- (Wheeler Publishing Large Print, 2015)
"'There are books that are suitable for a million people, others for only a hundred. There are even remedies--I mean books--that were written for one person only...A book is both medic and medicine at once. It makes a diagnosis as well as offering therapy. Putting the right novels to the appropriate ailments: that's how I sell books.' Monsieur Perdu calls himself a literary apothecary. From his floating bookstore in a barge on the Seine, he prescribes novels for the hardships of life. Using his intuitive feel for the exact book a reader needs, Perdu mends broken hearts and souls. The only person he can't seem to heal through literature is himself; he's still haunted by heartbreak after his great love disappeared. She left him with only a letter, which he has never opened. After Perdu is finally tempted to read the letter, he hauls anchor and departs on a mission to the south of France, hoping to make peace with his loss and discover the end of the story. Joined by a bestselling but blocked author and a lovelorn Italian chef, Perdu travels along the country's rivers, dispensing his wisdom and his books, showing that the literary world can take the human soul on a journey to heal itself."--